Analysis of Product Quality, Service Quality, Promotion, Emotionality on Customer Satisfaction at Mojo Resto Medan - Nurafrina Siregar (Yayasan Multidimensi Kreatif, 2023)
This research aims to analyze and test the influence of product quality, service quality, promotions and emotions on customer satisfaction at Mojo Resto Medan. The type of research used is associative quantitative. The population in this study were Mojo Resto Medan customers, and the sample selected was 97 samples using random sampling. Data collection techniques were carried out using questionnaires, observations and interviews. The research results show that product quality has a significant positive effect on customer satisfaction with a positive correlation of 0.298 and a significance of 0.001. Service quality has a significant positive effect on customer satisfaction with a positive correlation of 2.037, significance of 0.045. Promotion has a significant positive effect on customer satisfaction with a positive correlation of 0.340, significance of 0.000. The promotion variable has the strongest influence on customer satisfaction compared to other independent variables. Emotionality has a significant positive effect on customer satisfaction. Product quality, service quality, promotions and emotions simultaneously have a significant positive effect on customer satisfaction at Mojo Resto Medan. Coefficient determination shows a result of 42%, meaning product quality, service quality, promotion, And emotional contribute And give 42% influence on customer satisfaction at Mojo Resto Medan.